Предмет: Алгебра, автор: koymemail

Выполнить умножение:
а) 2х(х2 + 8х – 3),

б) -3а(а2 + 2ав – 5в),

в) 4х3(ах2 + а3х – 2а2).


Упростить выражение:
а) -2х(х + 4) +5(х2 – 3х),

б) 2а(3а – а2) – 4а(2а2 – 5а),

в) х(2х – 1) -3х( 3 – х).


Решить уравнение:
а) 5х(х- 4) –х(3 + 5х) =4,

б) 7х – 2х2 + 4 = х(5 – 2х),

в) 2х(3х – 2) -3(х2 – 4х) =

= 3х(х – 7) +2.

Ответы

Автор ответа: Санечка69
4

1. Выполнить умножение:

     а) 2х(х² + 8х - 3) = 2х³ + 16х² - 6х;

     б) -3а(а² + 2аb - 5b) = -3а³ - 6а²b + 15аb;

     в) 4х³(aх² + a³x - 2a²) = 4ax⁵ + 4a³x⁴ - 8a²x³.

2. Упростить выражение:

     а) -2х(х + 4) + 5(х² - 3х)= -2x² - 8x + 5x² - 15x = 3x² - 23x;

     б) 2а(3а - а²) - 4а(2а² - 5а) = 6a² - 2a³ - 8a³ + 20a² = -10a³ + 26a²;

3. Решить уравнение:

     а) 5х(х - 4) - х(3 + 5х) = 4,

          5х² - 20х - 3х - 5х² = 4,

          -23х = 4,

          х = -4/23;

     б) 7х - 2х² + 4 = х(5 - 2х),

          7x - 2x² + 4 = 5x - 2x²,

          7x - 2x² - 5x + 2x² = -4,

          2x = -4,

          x = -2;

      в) 2х(3х - 2) - 3(х² - 4х) = 3х(х - 7) + 2,

          6x² - 4x - 3x² + 12x = 3x² - 21x + 2,

          3x² + 8x = 3x² - 21x + 2,

          3x² + 8x - 3x² + 21x = 2,

          29x = 2,

          x = 2/29.

Похожие вопросы